Aktivitas Manajemen Laba Melalui Pos Advertising Expense - Cindy Riady; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to prove that the management had done earnings management through the real activities of advertising on companies in the consumer sector. The existence of earnings management through the real activities of advertising could be seen from the abnormal advertising expense. This study used EPS as the basis for the grouping of samples of companies that had done earnings management and companies had not do earnings management (suspect firms). This study used control variables of firm size, market to book ratio, and return on assets. This study examined the 27 companies in the consumption sector listed in Indonesia Stock Exchange with a sample of 52 observations. The results showed that the management of suspect firms had done earnings management by the reduction of the real activities of advertising. The research results also showed that market to book ratio had a significant positive affect on earnings management by the reduction of the real activities of advertising and firm size had a significant negative affect on earnings management by the reduction of the real activities of advertising, while the return on assets had no affect on earnings management by the reduction of the real activities of advertising.